Clean Water Treatment for Public Health in Indonesia: A Review - Waode Evi Frianti; Vera Hendrawanti; Azahrah Wulandari (Journal of Epidemiology and Health Science, 2026)
Background: Clean water is a fundamental human need essential for drinking, cooking, sanitation, and other daily activities. Water quality is closely associated with public health because contaminated water can transmit infectious diseases such as diarrhea, cholera, dysentery, and skin infections. Rapid population growth and urbanization have increased the demand for clean water, while many raw water sources require treatment before they are safe for consumption. Objective: This study aimed to analyze the stages of clean water treatment, including coagulation, flocculation, sedimentation, filtration, and disinfection, and evaluate their effectiveness in producing water that meets health standards. Methods: A literature review was conducted using 25 national and international journal articles retrieved from Google Scholar. Data were analyzed descriptively by comparing the effectiveness of each treatment stage in improving water quality. Results: The review showed that each treatment stage plays a complementary role in removing suspended particles, organic matter, microorganisms, and other contaminants. Combined treatment processes consistently improved water quality and reduced health risks. Conclusion: Effective water treatment is essential for ensuring safe water supplies and protecting public health. Strengthening infrastructure and treatment systems remains necessary to improve water access and quality. Keywords: water treatment, coagulation, flocculation, sedimentation, filtration, disinfection.